"God within Us": Christianity and Subversion in Ngũgĩ wa Thiong'o's Fiction. (2nd September 2017) - Andindilile, Michael
ABSTRACT: This paper focuses on Kenyan writer, Ngũgĩ wa Thiong'o's paradoxical engagement with Christianity and its topology. Against his increasingly hostile attitude towards the Christian establishment in a post-colonial space, the paper interrogates how this writer, who has been dubbed a "religious writer, " deploys Christianity and its topology as a conduit for his subversion in his fiction. Partly informed by Stephen Greenblatt's seminal essay "Invisible Bullets" and its conception of containment and subversion, the article examines how Ngũgĩ uses Christianity and its topology to advance his literary and rhetorical agenda of exposing and questioning colonial and neo-colonial social injustices, hence turning such imagery and topology into powerful literary and rhetorical tools that embody the subversion of his works. Although colonialism and its link to the spread of Christianity has been exploited by many African writers in dialogical and syncretic ways characterised by subtle shades of meaning and expressions, Ngũgĩ has gone a step further to deploy to his aesthetic and rhetorical advantage the same Christianity that he attacks so fiercely. The paper also examines how the purpose and degree to which Ngũgĩ deploys Christianity as a constant subject and conduit of his subversive writing varies from his apprentice novels to his hard-hitting and ideologically astute and conscious novels. It contends that Ngũgĩ's subversion lies in both the implicit and explicit use of Christian imagery and typology as a conduit for conveying subversive messages that denounce manifestations of exploitation found in his native Kenya, in particular, and other African nation-states in general.